2019
DOI: 10.1097/sla.0000000000002553
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Decision Analytical Modeling in Surgical Research

Abstract: The results show how decision analytical modeling can help to identify relevant uncertainty and guide decisions for future research in surgery. Based on the current available evidence, a randomized clinical trial on complications, hospital stay, costs, quality of life, and survival is highly unlikely to change the conclusion that LDP is more cost-effective than ODP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Our findings add to existing evidence associating MIDP with reduced perioperative blood loss, time to functional recovery, length of stay, and impact on quality of life 6–9,18 . MIDP has been shown cost-effective in a decision-analytic model based on pooled observational data 45 . In addition, a cost analysis of the LEOPARD trial data found no excess costs for MIDP compared with ODP 46 .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Our findings add to existing evidence associating MIDP with reduced perioperative blood loss, time to functional recovery, length of stay, and impact on quality of life 6–9,18 . MIDP has been shown cost-effective in a decision-analytic model based on pooled observational data 45 . In addition, a cost analysis of the LEOPARD trial data found no excess costs for MIDP compared with ODP 46 .…”
Section: Discussionsupporting
confidence: 66%
“…[6][7][8][9]18 MIDP has been shown cost-effective in a decision-analytic model based on pooled observational data. 45 In addition, a cost analysis of the LEOPARD trial data found no excess costs for MIDP compared with ODP. 46 The association between conversion and increased composite major morbidity in the ACS-NSQIP population was not confirmed upon external model validation nor in the LEOPARD trial.…”
Section: Discussionmentioning
confidence: 99%
“…One other previous study used decision-analytical modelling to create different scenarios and likewise found laparoscopic distal pancreatectomy to be dominant compared to open resection. 168 The assumptions for the model, however, were based on data from nonrandomized trials, which might make them less reliable.…”
Section: Discussionmentioning
confidence: 99%